A management and visualization framework for reconfigurable WDM optical networks. - Liu, K.H (IEEE Network : the magazine of global information exchange)
As the phenomenal advance in optical WDM networking technologies continues, optical WDM network equipment has been deployed not only in backbone networks, but also in regional, metropolitan, and access networks. It is widely believed that a major component of the next-generation Internet will be an IP-based optical network employing WDM. WDM wavelength routing and signaling have become an active research field, and dynamic and adaptive wavelength routing and assignment algorithms have been proposed. However, there is less work on reporting network control and management system implementation efforts over testbed WDM networks. This article presents a network management and visualization framework aimed at guiding the development of management applications for reconfigurable WDM optical networks. A layered framework architecture including element and network management and visualization is provided, and an object-based information model representing the WDM network is introduced. Functional components on reconfiguration, software agent, and network visualization services are presented, and important issues related to optical lightpath generation are discussed. A network visualization service also provides WDM control and management APIs to applications and access networks such as an IP network management system. To illustrate the usage of the framework, we share our experience in implementing the MONET network control and management system, and present network visualization views obtained from the MONET WDM network to highlight the framework features.